(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to prepare an educational curriculum according to the Keeler model in developing motor flexibility and learning the skill of serving in tennis and identifying the impact of the curriculum. Al-Mustansiriya for the academic year 2022-2023; The percentage of the sample was (7.46%) of the original population. The sample was chosen randomly, as it was divided into two groups (20) students as an experimental group and (20) students as a control group. The researcher concluded that the educational curriculum according to the Keeler model has a positive impact on the development of motor flexibility and learning the skill of serving in tennis.